2006
DOI: 10.1002/ijc.22202
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of fatty acid synthase and progesterone receptor in early steps of human mammary carcinogenesis

Abstract: Progestins increase the risk of breast cancer in the hormone therapy of menopause, and progesterone receptor-induced fatty acid synthase (FAS) is a potential therapeutical target of breast cancer. In a first attempt to specify in which lesions at risk of breast cancer progestins might be acting, we have compared the progesterone receptor (PR) and FAS expression in preinvasive breast lesions and in adjacent ''normal'' mammary glands. We used archive paraffin-embedded tissues from 116 patients, with 164 lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 32 publications
2
25
0
2
Order By: Relevance
“…Their findings are comparable to ours, though this group did not describe the suprabasal cell staining seen in the current study. The authors 19 suggest that these findings are most likely in keeping with epithelial stem cells because of the topographic location. These results provide endorsement for the proposal by some that FASN expression may reflect increased membrane synthesis and cell growth, as supported by studies of the gastrointestinal tract, brain and genitourinary system.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Their findings are comparable to ours, though this group did not describe the suprabasal cell staining seen in the current study. The authors 19 suggest that these findings are most likely in keeping with epithelial stem cells because of the topographic location. These results provide endorsement for the proposal by some that FASN expression may reflect increased membrane synthesis and cell growth, as supported by studies of the gastrointestinal tract, brain and genitourinary system.…”
Section: Discussionmentioning
confidence: 90%
“…Double-staining experiments indicate that FASN-positive cells do not exhibit a characteristic 'basal' (cytokeratin 5/6-positive) or myoepithelial (p63-positive) immunophenotype. Esslimani-Sahla et al 19 have also described FASN immunoreactivity through a monoclonal FASN antibody as a scattered expression pattern in normal and pathological structures of epithelial mammary cells. Their findings are comparable to ours, though this group did not describe the suprabasal cell staining seen in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…By immunohistochemistry, in studying the early stages of breast carcinogenesis, we detected a statistically significant increased level of PR and FASN level in proliferating breast lesions in comparison to adjacent normal tissues [52] (Fig. 3).…”
Section: Prs In Breast Cancermentioning
confidence: 89%
“…Accordingly, we found that FASN and HER2/ Neu upregulation were strongly correlated in high-grade DCIS [52] as it is in the HER 2/Neu invasive breast cancers [54]. Other mechanisms than increased PR level can facilitate progesterone activity, such as gene amplification of the co-activator AIB1 [55], an unbalance in breast cancer between the two PR isoforms A and B [56], or a decreased level of a competitor.…”
Section: Prs In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation